LEADERSHIP EFFECT AND MOTIVATION ON PERFORMANCE OF EMPLOYEES AT THE DEPUTY FOR COORDINATION INVESTMENT AND MINING, COORDINATING MINISTRY FOR MARITIME AND INVESTMENT OF THE REPUBLIC OF INDONESIA - Bambang Nurakhim; Siti Ubaidah; Eddy Kusworo (Jurnal Ekonomi, 2022)
This study aims to analyze the effect of the Leadership variable (X1) and the Motivation variable (X2) on the Employee Performance variable (Y) at the Deputy for Investment and Mining Coordination, Coordinating Ministry for Maritime and Investment of the Republic Of Indonesia. This research uses a quantitative approach with a descriptive study method. Primary data are obtained from a closed questionnaire instrument and assessed using a Likert scale. The data analysis tool used is multiple linear regression analysis using the SPSS version 26 application. The sampling technique used is the sampling technique with the Slovin formula. From a total population of 68 people, 40 people were used as samples. The results showed that the influence of leadership and motivation on employee performance was 71.1%. It shows that 71.1% of Leadership (X1) and Motivation (X2) simultaneously affect Employee Performance (Y), while the remaining 28.9% is influenced by other factors not examined in this study. Optimizing the role of leadership and motivation needs to be pursued to improve employee performance so that in the future, it can be even better in improving services to the community.